Study and Analysis of the Factors that Affect the Efficiency of Small and Medium Enterprises in the Kingdom of Saudi Arabia - العميم, ناصر; احمد, مصطفى محمد (Journal of Economics and Administrative Sciences, 2019)
Encouraging micro-enterprises for comprehensive economic development are crucial to achieve the ambitious vision 2030 of the Kingdom of Saudi Arabia. Small and Medium enterprises are inputting around 15.5 per cent to GDP while 33 per cent contribution as a private sector to Saudi Arabia's gross domestic product (GDP). This study aims to identify the most important factors that affect the efficiency of small enterprises in Saudi Arabia. To accomplish this objective, the study was conducted for small projects via the comprehensive inventory method under the supervision of the Institute of Entrepreneurship. A total of 282 questionnaires were collected from entrepreneurs and the differentiation analysis was applied. The results of the data analysis revealed the existence of many administrative, marketing, financing and human as well as legislative factors affecting the efficiency of small and medium enterprises in Saudi Arabia. In the light of the results, a number of recommendations are suggested that could contribute to encouraging and enhancing the role of small and medium enterprises in achieving the ambitious vision 2030 of the Kingdom